2013
DOI: 10.3390/brainsci3020704
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Neural Circuit Dysfunction Following Developmental Ethanol Exposure

Abstract: Fetal Alcohol Spectrum Disorder (FASD) is a general diagnosis for those exhibiting long-lasting neurobehavioral and cognitive deficiencies as a result of fetal alcohol exposure. It is among the most common causes of mental deficits today. Those impacted are left to rely on advances in our understanding of the nature of early alcohol-induced disorders toward human therapies. Research findings over the last decade have developed a model where ethanol-induced neurodegeneration impacts early neural circuit develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 144 publications
(217 reference statements)
1
34
0
Order By: Relevance
“…GABA is known to be a critical modulator of brain development, and its reduction during critical periods alters normal development of cortical circuits (Le Magueresse & Monyer, 2013). In the adult, reduced GABA neurotransmission is thought to contribute to hyperexcitability and disrupted cortical oscillations that have been noted in various developmental disorders (Sadrian et al, 2013). Our findings that several gross features of cortex, such as thickness and laminar organization, are largely normal in the adult animal, is consistent with previous observations that the cortex has substantial capacity to overcome perinatal disruption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GABA is known to be a critical modulator of brain development, and its reduction during critical periods alters normal development of cortical circuits (Le Magueresse & Monyer, 2013). In the adult, reduced GABA neurotransmission is thought to contribute to hyperexcitability and disrupted cortical oscillations that have been noted in various developmental disorders (Sadrian et al, 2013). Our findings that several gross features of cortex, such as thickness and laminar organization, are largely normal in the adult animal, is consistent with previous observations that the cortex has substantial capacity to overcome perinatal disruption.…”
Section: Discussionmentioning
confidence: 99%
“…They have demonstrated that the effects of ethanol vary depending on the gestational timing of exposure. Treatment during the rodent early postnatal period, approximating the human third trimester, causes both widespread apoptotic cell death in the brain and long-lasting behavioral deficits (Ikonomidou et al, 2000; Sadrian, Wilson, & Saito, 2013; Wilson, Peterson, Basavaraj, & Saito, 2011; Wozniak et al, 2004). This is a period when neurogenesis is largely complete, and the brain is rapidly growing (Miller, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations